Prevalence of chronic kidney disease and associated factors among patients with underlying chronic disease at Dessie Referral Hospital, East Amhara Region, Ethiopia - Ali, Ahmed; Mulatu, Kebadnew; Feleke, Sefineh Fenta; Wassie, Gizachew Tadesse (Frontiers in Epidemiology, 2023)
Background Chronic kidney disease is defined as a reduction in glomerular filtration rate below 60 ml/min per 1.73 m2 and presence of albuminuria over a period of time. Globally, 10%–15% of populations are affected by chronic kidney disease. Studies conducted in Jimma, Addis Ababa, and the Tigray region were conducted on a single chronic disease and did not include human immune viruses. In addition, there has been no such study conducted in the Amhara region. Therefore, the aim of this study was to determine the magnitude and associated factors of chronic kidney disease among chronic patients who are followed up at an outpatient department. Methods An institutional-based cross-sectional study of 480 chronic patients was conducted at Dessie Referral Hospital, Dessie, Ethiopia between 15 March and 16 April 2020. Data were entered into Epidata and exported to SPSS version 25 for analysis. Binary logistic regression models were performed to identify factors associated with chronic kidney disease. The variables with a p-value ≤0.25 were considered to be a candidate for multivariable logistic regression. A p-value ≤0.05 was considered a statistically significant association. Results The magnitude of chronic kidney disease among the study participants was 21.3%. Variables such as hypertension [adjusted odds ratio (AOR): 2.6, 95% CI: 1.58–4.27], use of non-steroidal anti-inflammatory drugs (AOR: 2.4, 95% CI: 1.41–3.97), smoking (AOR: 4.4, 95% CI: 2.65–7.34), routine physical activity (AOR: 0.6, 95% CI: 0.35–0.94), and obesity (AOR: 3.0, 95% CI: 1.76–5.05) were significantly associated with the chronic kidney disease. Conclusion This study found that the magnitude of chronic kidney disease in the study area was high. Hypertension, use of non-steroidal anti-inflammatory drugs, smoking, routine physical activity, and obesity were found to be significant factors for chronic kidney disease.